2004
DOI: 10.1590/s1413-70542004000500012
|View full text |Cite
|
Sign up to set email alerts
|

Germinação in vitro de murici-pequeno (Byrsonima intermedia A. Juss.)

Abstract: RESUMOO murici-pequeno (Byrsonima intermedia A. Juss.), espécie medicinal do Cerrado, apresenta dificuldade de propagação sexuada decorrente da baixa taxa de germinação e emergência lenta das plântulas em campo. Objetivou-se com o presente trabalho estudar aspectos da germinação in vitro de murici-pequeno mediante avaliação do efeito dos meios de cultura MS e WPM e diferentes concentrações de BAP. Frutos maduros foram coletados de populações naturais, dos quais sementes e embriões foram excisados e utilizados … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
6

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 1 publication
0
6
0
6
Order By: Relevance
“…(Souza et al 2003) and Byrsonima intermedia A. Juss. (Nogueira et al 2004). Experiments with mature, immature and dry seeds of J. curcas also revealed that MS medium was efficient to sustain germination and continuous growth of plants under in vitro conditions (Nunes et al 2008).…”
Section: Discussionmentioning
confidence: 94%
“…(Souza et al 2003) and Byrsonima intermedia A. Juss. (Nogueira et al 2004). Experiments with mature, immature and dry seeds of J. curcas also revealed that MS medium was efficient to sustain germination and continuous growth of plants under in vitro conditions (Nunes et al 2008).…”
Section: Discussionmentioning
confidence: 94%
“…The culture medium used was WPM (LLOYD & McCOWN, 1980), with 50% of the salt concentration, no sucrose, 0.5 % agar and pH ajusted to 5.8 prior to autoclaving at 121°C for 20 minutes according to the protocol established by NOGUEIRA et al (2004); only one embryo was inoculated in each test tube (25x150mm) containing 10mL of WPM culture medium and each tube represented one replicate.…”
Section: Decontamination and In Vitro Culturementioning
confidence: 99%
“…(NOGUEIRA et al, 2004), Cereus jamacaru DC. (RÊGO et al, 2009), Genipa americana L. (ALMEIDA et al, 2013) and exotic species Moringa oleifera Lam.…”
Section: São Poucos Os Relatos Na Literatura Sobre Estudos Do Comportmentioning
confidence: 99%